A Colon‐Targeted Oral Probiotics Delivery System Using an Enzyme‐Triggered Fuse‐Like Microcapsule. Issue 8 (14th January 2021) - Cheng, Qikun; Liu, Lu; Xie, Mingzhi; Li, Hang; Ma, Dong; Xue, Wei
Abstract: Probiotics are closely related to human health. However, it is hard to find an appropriate disintegration mode for encapsulation to balance the survival, release, and adhesion of probiotics simultaneously during the current colon‐targeted oral delivery, which leads to limited colonization. In this study, an enzyme‐triggered fuse‐like microcapsule is constructed using alginate and protamine via the electrostatic droplet combined with the layer by layer self‐assembly. The multilayer microcapsule can protect the probiotics in the stomach and disintegrate layer by layer under the catalysis of trypsin in the intestine. The formulation with two protamine layers showed the best protection for Escherichia coli MG1655 (EM) during the oral delivery; as well the minimal release at the gastric pH value but a burst release after 1 h at the intestinal pH value. In particular, the adhesion strength of EM is improved with the increase of the layer number. In vivo experiments demonstrate that the EM enters into the stationary phase within 12 h in the colon. Moreover, the blood biochemistry and histological analysis demonstrates the safety of the microcapsule formulation. It can be concluded that this microcapsule can help the probiotics survive during the delivery, then release and colonize in the colon. Abstract : In the present work, an enzyme‐triggered fuse‐like microcapsule is constructed for the colon‐targeted oral probiotics delivery. By overcoming a series of physiological barriers, the microcapsule is detonated with the help of trypsin, which results in that the encapsulated probiotics can be released, then adhere, and colonize in the colon.